The suppressive effect of bacterial-feeding nematodes on hemocyte spreading of Galleria mellonella. (April 2021) - Ono, Masaya; Hayakawa, Yoichi; Hama, Yoichiro; Yoshiga, Toyoshi
Abstract: Insect parasitic nematodes have developed a mechanism to escape from the cellular immunity of their insect hosts for successful parasitism. However, the detailed mechanism whereby they achieve this remains unclear. In our previous study, we demonstrated that non-parasitic nematodes such as Caenorhabditis elegans potentially have the ability to escape from the cellular immunity of the greater wax moth Galleria mellonella . Here we aimed to clarify the effect of non-parasitic and parasitic nematodes on the spreading of hemocytes—an essential cellular reaction for adhering to a foreign substance —from G. mellonella larvae. The hexane/methanol extract of C. elegans inhibited the spreading of hemocytes. Using 2D-TLC and reversed-phase HPLC, we detected a single peak that inhibited the spreading of hemocytes. In addition, the spreading of hemocytes recovered from C. elegans -injected insects was significantly delayed. Western blotting analysis showed that phosphorylated extracellular signal-regulated protein kinase (ERK) —an essential signaling component for spreading in hemocytes—was decreased by the injection of C. elegans, and that plasma from nematode-injected insects contained the factor that causes the decrease of phosphorylated ERK. We also observed this phenomenon using other non-parasitic and parasitic bacterial-feeding nematodes. These results suggest that the factors inhibiting hemocyte adhesion and delaying the spreading of hemocytes are conserved in bacterial-feeding nematodes and could be a pre-adaptation for parasitism. Highlights: Nematode extracts inhibited insect hemocyte spreading in vitro. The extracts contained lipidic moiety. The spreading of hemocytes from a nematode injected-insect was significantly delayed. The phosphorylated ERK decreased in hemocytes from a nematode injected-insect. The plasma from a C. elegans injected-insect contained the factor that causes the decrease of phosphorylated ERK.